Kuhn''s ''The Structure of Scientific Revolutions'' : a Reader''s Guide. - Preston, John (Reader''s Guides., 2008)
Thomas Kuhn''s The Structure of Scientific Revolutions is arguably one of the most influential books of the twentieth century and a key text in the philosophy and history of science. Kuhn transformed the philosophy and history of science in the twentieth century in an irrevocable way and still provides an important alternative to formalist approaches in the philosophy of science. In Kuhn''s ''The Structure of Scientific Revolutions'': A Reader''s Guide, John Preston offers a clear and thorough account of this key philosophical work. The book offers a detailed review of the key themes and a l.